EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TERHADAP MOTIVASI DAN PEMAHAMAN SISWA PADA MATERI USAHA DAN ENERGI - Aji Bhaskara, Ferdian; Dinda Kusumaning Putri; Dhea Nanda Rahayu; Widya Sekar Ramadhani; Ridho Ramadhan; Ika Dewi Sumiati (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to describe the learning model implemented by the eighth-grade science teacher at SMPN 2 Jember for the topic of Work and Energy and to evaluate its effect on students’ motivation and understanding. The study used a descriptive qualitative approach with the researcher as the primary instrument, supported by interview guidelines and questionnaires. The subjects were one science teacher and 39 eighth-grade students. Data were collected through structured interviews with the teacher and a 4-point Likert scale questionnaire containing six items on motivation and four items on understanding. Data analysis was conducted descriptively using frequency counts and percentages. Interviews indicated that the teacher applied a cooperative learning model to enhance collaboration, interaction, and students’ social skills. Questionnaire results showed most students had positive motivation, with 42.31% Strongly Agree (SS) and 55.98% Agree (S), while 1.71% were Disagree (TS) and 0% Strongly Disagree (STS). Understanding responses were 43.59% Agree (SS), 46.79% While (S), 8.97% Disagree (TS), and 0.64% Strongly Disagree (STS). Findings confirm that cooperative learning improves engagement, enthusiasm, and understanding. This model provides an interactive and enjoyable learning experience, encouraging students to discuss and collaborate actively. Results are valuable for teachers in designing effective strategies and as a reference for further research on learning models effects on motivation and understanding.